2000
DOI: 10.1001/jama.284.8.972
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Mineral Density and Risk of Fracture in White Female Nursing Home Residents

Abstract: Our data indicate that low BMD and independence in transfer are significant predictors of osteoporotic fracture in white female nursing home residents. JAMA. 2000;284:972-977

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(117 citation statements)
references
References 33 publications
6
110
1
Order By: Relevance
“…Older studies reported the highest risk ratios in the youngest senior age strata [15,25]. For the LTC cohort, our incidence rates were similar to [15,27,28] or lower than [29,30] other published studies on institutionalized populations, particularly Chandler et al who reported a rate of 109 osteoporotic fractures per 1000 person-years [31]. Our reported rates in the community were higher than the community-based Canadian Multicentre Osteoporosis Study (CaMos) [32] although there are differences in study methodologies with CaMOS relying on patient selfreport.…”
Section: Discussionsupporting
confidence: 71%
“…Older studies reported the highest risk ratios in the youngest senior age strata [15,25]. For the LTC cohort, our incidence rates were similar to [15,27,28] or lower than [29,30] other published studies on institutionalized populations, particularly Chandler et al who reported a rate of 109 osteoporotic fractures per 1000 person-years [31]. Our reported rates in the community were higher than the community-based Canadian Multicentre Osteoporosis Study (CaMos) [32] although there are differences in study methodologies with CaMOS relying on patient selfreport.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, application of hip protectors in nursing homes by staff may be considered an important cointervention, not available in other group residence settings; this issue could be another contributor to clinical heterogeneity of pooled analyses of mixed populations. The nursing home population was of greatest clinical interest, as this population is known to be at extremely high risk for osteoporosis [14][15][16], falls [17], cognitive impairment (leading to falls and hip fracture) [16], and hip fracture [18][19][20].…”
Section: Selection Of Trials For Inclusion and Data Abstractionmentioning
confidence: 99%
“…Studies from the USA report osteoporosis prevalence of 4.3%-13% and 15.4%-51% in men and women over 50 years of age, respectively [29,30] . The prevalence of osteoporosis in Korea is 7.3% in men and 38% in women over 50 years of age [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies did not take such factors into account, and most of them pooled healthy subjects into the control group. Furthermore, quite high prevalence values concerning overall osteoporosis and vit D deficiency levels are given by numerous epidemiological studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . The condition is defined as a pandemic of osteoporosis and vit D deficiency by several sources [20,25] .…”
Section: Introductionmentioning
confidence: 99%